The reproducibility of 31-phosphorus MRS measures of muscle energetics at 3 Tesla in trained men - Edwards, L; Tyler, D; Kemp, G; Dwyer, R; Johnson, A; Holloway, C; Nevill, A; Clarke, K (Public Library of Science, 2012)
OBJECTIVE: Magnetic resonance spectroscopy (MRS) provides an exceptional opportunity for the study of in vivo metabolism. MRS is widely used to measure phosphorus metabolites in trained muscle, although there are no published data regarding its reproducibility in this specialized cohort. Thus, the aim of this study was to assess the reproducibility of (31)P-MRS in trained skeletal muscle. METHODS: We recruited fifteen trained men (VO(2)peak = 4.7±0.8 L min(-1)/58±8 mL kg(-1) min(-1)) and performed duplicate MR experiments during plantar flexion exercise, three weeks apart. RESULTS: Measures of resting phosphorus metabolites were reproducible, with 1.7 mM the smallest detectable difference in phosphocreatine (PCr). Measures of metabolites during exercise were less reliable: exercising PCr had a coefficient of variation (CV) of 27% during exercise, compared with 8% at rest. Estimates of mitochondrial function were variable, but experimentally useful. The CV of PCr(1/2t) was 40%, yet much of this variance was inter-subject such that differences of <20% were detectable with n = 15, given a significance threshold of p<0.05. CONCLUSIONS: 31-phosphorus MRS provides reproducible and experimentally useful measures of phosphorus metabolites and mitochondrial function in trained human skeletal muscle.